Liquid Biopsies in Cancer Diagnosis - R.Sharmila1 , Anitha Roy2 , K. Anjaneyulu3 , Lakshmi.T4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Over many years, the concept of precision medicine has dramatically renewed the sphere of clinicaloncology; the advent of patient-tailor-made therapies has appreciably stepped forward all measurableoutcomes. Liquid biopsy is a modern method that commences unexpected perspectives. It includes thedetection and isolation of circulating tumor cells, circulating tumor DNA and exosomes, as a supply ofgenomic and proteomic records in patients with most cancers. Many technical hurdles had been resolved tonewly advanced techniques and subsequent-generation sequencing analyses, permitting a wide software ofliquid biopsy in a huge variety of settings. Initially correlated to analysis, liquid biopsy facts at the momentare being studied for cancer analysis, with a bit of luck consisting of screenings, and most significantlyfor the prediction of reaction or resistance to given remedies. In specific, the identification of particularmutations in genes can be useful resources in therapeutic choices, both in the appropriateness of remedy andwithin the superior identity of secondary resistance, aiming to early diagnose disease progression. Still, theutility is far from fact however ongoing research is leading the manner to a new era in oncology. The mainaim of this study is to assess the importance of liquid biopsy in cancer diagnosis.